Peacemaking and international order after the First World War - Jackson, Peter 1964-; Mulligan, William 1975-; Sluga, Glenda 1962- (Cambridge University Press, 2023)
The Paris peace settlements following the First World War remain amongst the most controversial treaties in history. Bringing together leading international historians, this volume assesses the extent to which a new international order, combining old and new political forms, emerged from the peace negotiations and settlements after 1918. Taking account of new historiographical perspectives and methodological approaches to the study of peacemaking after the First World War, it views the peace negotiations and settlements after 1918 as a site of remarkable innovations in the practice of international politics. The contributors address how a wide range of actors set out new ways of thinking about international order, established innovative institutions, and revolutionised the conduct of international relations. They illustrate the ways in which these innovations were merged with existing practices, institutions, and concepts to shape the international order that emerged out of the Paris Peace Conference of 1919
Title from publisher's bibliographic system (viewed on 22 May 2023)
Introduction / Peter Jackson, William Mulligan, and Glenda Sluga -- Vocabularies of self-determination in 1919 : the co-constitution of race & gender in international law / Sarah C. Dunstan -- Recasting the "fabric of civilization" : the Paris Peace Settlement and international law / Marcus M. Payk -- State sovereignty / Leonard V. Smith -- The crisis of power politics / Peter Jackson and William Mulligan -- The challenge of an absent peace in the French and British Empires after 1919 / Martin Thomas -- A 'new diplomacy'? : The big four and peacemaking, 1919 / Alan Sharp -- The League of Nations : the creation and legitimisation of international civil service / Karen Gram-Skjoldager -- The enforcement of German disarmament and the international order of the 1920s / Andrew Webster -- Planning for international financial order : the call for collective responsibility at the Paris Peace Conference / Jennifer Siegel -- Raw materials and international order from the Great War to the Crisis of 1920-21 / Jamie Martin -- The great conversation : discussion on peace after the First World War / Carl Bouchard -- An alternative international relations : socialists, socialist internationalism and the postwar order / Talbot Imlay -- The Paris Peace Conference and the origins of global feminism / Mona L. Siegel -- Colonial nationalists and the making of a new international order / Erez Manela -- The persistence of old diplomacy : the Paris Peace Settlement in perspective / T. G. Otte -- Afterword: New histories of international order / Glenda Sluga
Keywords: Paris Peace Conference (1919-1920); League of Nations; Pariser Friedenskonferenz -- 1919-1920 -- Paris; World War, 1914-1918 / Peace; International organization / History; Peace-building / History; Diplomacy / History; World politics / 1919-1932; Internationale Politik; Nachkriegszeit; Erster Weltkrieg; Friedenssicherung; Internationales politisches System